Catalytic hydrodeoxygenation of biomass-derived oxygenates to bio-fuels over Co-based bimetallic catalysts. Issue 9 (30th June 2020) - He, Zhen-Hong; Jiang, Chong-Shan; Wang, Zhong-Yu; Wang, Kuan; Sun, Yong-Chang; Yao, Man-Qing; Li, Zhu-Hui; Liu, Zhao-Tie
Abstract : A versatile Co5 Zn1 O x bimetallic catalyst was developed and used in hydrodeoxygenation of biomass-derived oxygenates to bio-fuels with high efficiencies. Abstract : The rapid consumption of conventional fossil fuels has caused a sharp decline in their reserves and led to climate change. Exploitation of renewable energy sources especially bio-fuels such as 2, 5-dimethylfuran (DMF), methylfuran (MF), γ-valerolactone (GVL), etc. has both environmental and economic benefits. In the present work, diverse Co-based bimetallic catalysts were prepared and used for catalyzing hydrodeoxygenation (HDO) of biomass-derived oxygenates. Co5 Zn1 O x, obtained by the incorporation of Zn species into the Co metal catalyst especially with a Co/Zn molar ratio of 5, could enhance the catalytic performances obviously compared to the sole Co catalyst. For example, the DMF, MF, and GVL yields reached up to 94, 98, and 77% during the catalysis by Co5 Zn1 O x, which were much greater than 74, 0, and 23% for the Co catalyst, respectively. The enhanced performances of Co5 Zn1 O x stem from the strong interaction between the Co and Zn species. Specifically, the presence of ZnO could stabilize Co 2+ species, by offering electrons to Co species and creating oxygen vacancies, resulting in Co5 Zn1 O x showing the highest adsorption amounts of furfural and furfuryl alcohol compared to Co1 Zn1 O x and Co7 Zn1 O x catalysts. Moreover, the catalyst showed good universality and reusability, and the HDO of 5-HMF to DMF proceeded in a true heterogeneous manner. The present work is believed to extend the application of bimetallic catalysts to the synthesis of bio-fuels and utilization of biomass materials.